2004
DOI: 10.1002/mats.200300054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Cellulose Oligomers: Conformational Analysis

Abstract: Summary: The results of classical molecular simulations of cellulose oligomers are presented here. The conformations of the chains in the high temperature melt, room temperature quenched melt and gas phase are compared with respect to various geometrical parameters including square end‐to‐end distances, glycosidic link torsion correlations, ring puckering and hydrogen bonding. The cellulose oligomer melts were relaxed at 800 K with molecular dynamics, and then cooled down in three different ways to obtain dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The original publication is available at Springer via http://dx.doi.org/ 10.1007/s10570-014-0343-y increment of the temperatures. Queyroy et al (2004) studied the MD simulation of tetraose and octaose of cellulose and observed that most of the glucopyranose rings assumed a puckered un-chaired conformation at ~527 ˚C. As the decomposition of cellulose was considered to relate to the ring conformation change, the evaluation of the conformational changes would be important (Hosoya et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The original publication is available at Springer via http://dx.doi.org/ 10.1007/s10570-014-0343-y increment of the temperatures. Queyroy et al (2004) studied the MD simulation of tetraose and octaose of cellulose and observed that most of the glucopyranose rings assumed a puckered un-chaired conformation at ~527 ˚C. As the decomposition of cellulose was considered to relate to the ring conformation change, the evaluation of the conformational changes would be important (Hosoya et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, determination of DL/L can be reduced to Dl/l, which in turn can be evaluated from the end-to-end distance of the amorphous cellulose chain along the longitudinal axis of the microfibril. It is difficult to know the actual behavior of the cellulose chain when both ends may be bound to a crystalline region, though some researchers reported the simulation of conformation of single cellulose chain in this regard (for example Queyroy et al 2004). Additionally, the end-to-end distance of the cellulose chain appears to be slightly influenced by non-crystallization because of a non-flexible polymer chain.…”
Section: Simulation Of the Anisotropic Dimensional Changementioning
confidence: 94%
“…The degree of contraction calculated from the ratio of end-to-end distance to contour length was about 0.10-0.20. According to analyses of single cellulose chains by Queyroy et al (2004), the end-toend distance of a chain consisting of eight glucose residues with a contour length of 4.4 nm is about 3.2 nm. This corresponds to a 0.30 contraction.…”
Section: Simulation Of the Anisotropic Dimensional Changementioning
confidence: 99%
“…1 For decades, carbohydrates have been the focus of many experimental, spectroscopic, and computational investigations. Studies include the exploration of the conformational space and structural properties of mono-, [2][3][4][5][6][7][8][9][10][11][12] di-, [13][14][15][16] oligo-, and polysaccharides, [17][18][19][20] chemical reactions (condensation and isomerization, [21][22][23][24][25][26] hydrogen abstraction 27 and (photo-)fragmentation [28][29][30][31] ) and the computation of vibrational spectra. [32][33][34] Progress has also been made in the computational simulation of the structure of biopolymers such as cellulose 35,36 as well as computations of their physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%